Efek Perkembangan Komunikasi Massa Terhadap Pola Pikir dan Perilaku Masyarakat Di Era Society 5.0 - Muhamad Bisri Mustofa; Agus Sujepri; Nurrohman; Umiatul Mutoharoh; Vika Anggraini (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2022)
The involvement of technology in modern life can no longer be ignored. Almost all the activities of today's society can not be separated from technology. It is also to fulfill access in finding information. The involvement of the communication media is considered to be able to effectively complement the diverse needs of the community, the speed of access to information that currently varies. The media of mass communication has become an inexhaustible part of providing information to the audience, the life of print media and technology has become an inseparable component of human life. The ease in accessing mass communication media by the community, has an influence on changes in people's mindsets and behavior so as to make mass communication media as a benchmark. The purpose of this study was to determine the development of the effect of mass communication on people's mindset and behavior. This study uses a literature study method, namely by collecting data through written documents or electronic documents to support the writing process. This research shows that the mindset and behavior of the community is closely related to the development of mass communication media that is easily accessible anytime and anywhere